Existence of square-mean almost periodic mild solutions to some nonautonomous stochastic second-order differential equations - Paul H. Bezandry; Toka Diagana (Electronic Journal of Differential Equations, 2010)
In this paper we use the well-known Schauder fixed point principle to obtain the existence of square-mean almost periodic solutions to some classes of nonautonomous second order stochastic differential equations on a Hilbert space.